Effect of preparation rotation speed on structural properties ofCH3NH3PB1-xSnxCl3 using spin coating methods - Kemerchou , Imad . Hima, Abdelkader (University of Eloued جامعة الوادي, 2024)
Perovskite-based hybrid organic-inorganic solar cells that use the methylammonium lead tri-iodide (CH3NH3PbI3) have demonstrated ever-increasing energy conversion efficiency and low processing costs, comparable to that of high-efficiency silicon-based solar cells. However, it is suffuring from instability caused by material degradation. Recently, enhancing stability and hence decreasing the degradation process of CH3NH3PbI3based solar cells is one of the main topics of research in photovoltaic field. The poor stability of these cells prevents their commercialization despite their huge potential that exceeds conventional solar cells. The energy efficiency and economic viability of Perovskite cells depend primarily on the rate of degradation caused by light, temperature, moisture, and oxygen. This paper presents a review of different degradation sources of CH3NH3PbI3-based Perovskite solar cells (PSCs). In this work, a deposition of a CH3NH3PB1- xSnxCl3 Perovskite layer using spin coating method has been investigated. Therefore, different rotation speed have been used in layer spin coating phase to find out their effects on structural parameters characteristics of the resulting CH3NH3PB1-xSnxCl3 organic/inorganic Perovskite material.
Article
Keywords: Structural properties; Perovskite films; Spin coating; CH3NH3PB1-xSnxCl3